Bored gamers: applying the Meaning and Attentional Components model of boredom to digital game selection - Daneels, Rowan; Poels, Karolien; Vandebosch, Heidi (Frontiers in Communication, 2025)
IntroductionCommunication research has typically examined boredom as a negative emotion characterized by low arousal or understimulation. However, this one-dimensional approach to boredom does not resonate with more recent psychological insights, as summarized in the Meaning and Attentional Components (MAC) model. This model proposes several boredom types based on individuals’ attention levels (low versus high cognitive resources) and how meaningful an activity is to them. The model predicts that, depending on the boredom type, individuals switch to either enjoyable or interesting activities to regulate their boredom. Explicating these hypotheses in a communication research context, enjoyable activities could be linked to hedonic and interesting activities to eudaimonic media experiences. Although switching to media seems like an obvious choice when people experience boredom, the MAC model has yet to be empirically tested in a media context.MethodsUsing an online vignette-style survey among 581 players, we tested the aforementioned hypotheses in the context of digital games, examining how gaming serves as a positive way to regulate the negative emotion of boredom.ResultsFindings indicated that 74% of respondents were likely to switch to a digital game while experiencing boredom. Furthermore, bored individuals with low cognitive resources selected games offering hedonic experiences (i.e., fun, psychological detachment, and relaxation), consistent with the MAC model. However, bored individuals with high cognitive resources also preferred games with hedonic experiences over eudaimonic ones (i.e., appreciation, mastery, and control), contradicting our hypotheses.DiscussionSince few differences in game selection were observed across boredom profiles, we further discuss the MAC model’s usefulness in media content selection, the specific context of game selection, and the study’s limitations.